THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL JUSTICE ON WORK SATISFACTION THROUGH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DURING THE CONSOLIDATION PERIOD OF THE STATE-OWNED PHARMACEUTICAL HOLDING : (A Study At PT Bio Farma (Persero)) - Andhini Fauzia; Fansuri Munawar (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to analyze the effects of Transformational Leadership (X1) and Organizational Justice (X2) on employees' Work Satisfaction (Y) at PT Bio Farma (Persero), both directly and through the mediation of Organizational Citizenship Behavior (OCB). In the context of the transformation of the State-Owned Enterprises (BUMN) Pharmaceutical Holding initiated in 2020, the company faces challenges in maintaining employee satisfaction amid structural and policy changes. Methods: This research uses a quantitative approach with a survey involving 300 permanent employees of PT Bio Farma (Persero). The results of the study indicate that Transformational Leadership (X1) has an adverse direct effect on Work Satisfaction (Y), but a positive effect through the mediation of OCB. Organizational Justice (X2) has a positive direct impact on Work Satisfaction and also contributes to increased job satisfaction through OCB. Results: These findings suggest that although Transformational Leadership does not directly enhance Work Satisfaction, the mediating role of OCB significantly contributes to creating a work environment that supports employee satisfaction. It is recommended to strengthen Transformational Leadership and to implement clearer Organizational Justice principles to create a harmonious, productive work environment, ultimately increasing employee satisfaction. These findings are expected to contribute to the development of human resource management theory and provide practical recommendations for the company to improve organizational effectiveness by enhancing employee job satisfaction. Keywords: Organizational Citizenship, Behavior, Organizational Justice, Transformational Leadership, Work Satisfaction